IMPROVEMENT OF ADAPTATION TO STRUCTURES REMOVABLE DENTURES IN PATIENTS WITH ISCHEMIC HEART DISEASE - N.A. Ryabushko; V.N. Dvornik; I.V. Pavlish; G.N. Balya (Ukrainian Medical Stomatological Academy, 2016)
The aim is to improve the process of adaptation to removable designs of dentures in patients with coronary heart disease. To achieve this goal, we examined 81 patients aged from 42 to 67 years. • (basic) group consisted of 53 patients who underwent orthopedic structures removable dentures (removable partial dentures plastinochnyh (CHZPP) and who had a history of major diseases - coronary heart disease, stable exertional angina FC II - III FC. • group - 31 patients who received the combination treatment together with a cardiologist (antiplatelet therapy and dental treatment) who were administered and health care complex. The control group was involved 28 people aged 42 to 60 who belonged to the second group of health by the WHO classification. Patients of the main group after treatment of the underlying disease and the appointment of conservative treatment in 7-20 days time held dental treatment (prosthetics partial removable dentures plastinochnyh the appointment of health-care complex). The proposed health care was a complex algorithm to use: softener oral "Corsodyl" - 3-5 times a day after meals; clean teeth and dentures 2 times a day (morning and bedtime) toothpaste "Parodontax" and the bath solution Rinhra 3-5 times a day, with dryness in the mouth For the functional assessment made dentures were designed by us and proposed to use two methods of assessing patients to adapt designs removable dentures: • Objective evaluation - "Method of determining the degree of adaptation to the designs of removable dentures," Ukraine patent for utility model №101852 of 12.10.15; • Subjective evaluation - "Method of accelerated determination adaptation of patients to removable dentures designs using screening test" certificate of registration of copyright Ukraine №59280 15.04.2015. The first questionnaire includes only clinical data fills a dentist and does not reflect the subjective feelings of the patient. The second profile is completely based on the coverage of their own feelings patient and filled only patient. According to these questionnaires, we determined the degree of adaptation of patients to removable designs of dentures and compared its components. Questioning was conducted immediately after the prosthesis after 30 days and after 80-100 days of treatment. The results of the survey of patients with coronary heart disease before and after the use of health-care complex, we have concluded that improving the general feeling of patients diminish dryness of the mouth (40.9%) and discomfort when using dentures (29, 2%), thus improving adaptation to removable designs of dentures.